Cystic fibrosis transmembrane conductance regulator-dependent up-regulation of Kir1.1 (ROMK) renal K+ channels by the epithelial sodium channel. - Konstas, A; Koch, J; Tucker, S; Korbmacher, C (2002)
The epithelial sodium channel (ENaC) and the secretory potassium channel (Kir1.1/ROMK) are expressed in the apical membrane of renal collecting duct principal cells where they provide the rate-limiting steps for Na(+) absorption and K(+) secretion. The cystic fibrosis transmembrane conductance regulator (CFTR) is thought to regulate the function of both ENaC and Kir1.1. We hypothesized that CFTR may provide a regulatory link between ENaC and Kir1.1. In Xenopus laevis oocytes co-expressing both ENaC and CFTR, the CFTR currents were 3-fold larger than those in oocytes expressing CFTR alone due to an increased expression of CFTR in the plasma membrane. ENaC was also able to increase Kir1.1 currents through an increase in surface expression, but only in the presence of CFTR. In the absence of CFTR, co-expression of ENaC was without effect on Kir1.1. ENaC-mediated CFTR-dependent up-regulation of Kir1.1 was reduced with a Liddle's syndrome mutant of ENaC. Furthermore, ENaC co-expressed with CFTR was without effect on the closely related K(+) channel, Kir4.1. We conclude that ENaC up-regulates Kir1.1 in a CFTR-dependent manner. CFTR may therefore provide the mechanistic link that mediates the coordinated up-regulation of Kir1.1 during the stimulation of ENaC by hormones such as aldosterone or antidiuretic hormone.